The Effect of Moodle E-Learning on Students Writing Achievement at SMA Negeri 1 Kodeoha Kolaka Utara - Rahmatang, Rahmatang; Mursalim, Mursalim; Muhsin, Muhammad Khusnun (Universitas Halu Oleo, 2022)
The objective of this study was to find out whether Moodle E-learning has a significant effect on students' writing achievement at SMAN 1 Kodeoha or not. This research used pre-experimental design. The population of this study were all of the X grade of math and science students. The sample of this research were 28 students at X MIPA 1 class which consisted of 12 females and 16 males. The sample taken by using random sampling. The instrument of this research was writing test and used five writing’s components of ESL composition rubric profile by Jacobs (1981) namely content, organization, vocabulary, grammar and mechanics. To collect the data, the researcher giving pre-test, the treatment by using Moodle E-Learning and also giving post-test. In analyzing the data, the researcher used SPSS 20.0 version and used paired sample t-test to test the hypothesis of this study. The result of this study showed that students’ mean score were 64.58 at pre-test and 86.66 at post-test. As the result, the mean score of post - test was higher than in pre-test. Based on the calculation of t-test, it showed that the score of t- t-test = 14.424 was higher than t-table = 2.051 and the p-value = 0.000 was lower than = 0.05. Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. This can be concluded that Moodle E-learning has a significant effect on students' writing achievement at SMAN 1 Kodeoha, Kolaka Utara. Therefore, in improving students writing competence, Moodle E-learning can be used as one of effective methods on upgrading students ‘writing achievement.